Pengaruh Bioaktivator Mol Tapai Pada Proses Pengomposan Limbah Lumpur Kelapa Sawit Yang Disterilkan - Putri, Novia Eka; Yenie, Elvi; Daud, Syarfi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Natural composting process takes a long time so many products developed bio-activator such as Mol. This study aims to determine the effect of concentration of activators Mol Tapai on the quality of the compost produced. Composting methods do facultative. Composting is done in the reactor to the size of the reactor used with d1 = 28 cm; d2 = 28 cm; t = 40 cm; air exchange hole diameter of 1 cm to 5 cm distance between holes. Variables used are sterile compost raw material variation and non-sterile as well as variations in the number of Mol Tapai is 200 ml, 250 ml, and 300 ml each treatment. Composting research results with a variety of raw materials by variation Mol fermented sterile 250 ml obtain C / N ratio and a high of 11.35% in non-sterile raw material variation with 250 ml Mol variation of 10.67%, which is in accordance with SNI 19-7030 -2004 about the specifics of mature compost.Keywords: Mol Tapai, palm oil sludge, compost